Perceptions of Physical Activity and Sport Science students on professional competences for labor practice - Molina-García, Nuria; González-Serrano, Maria Huertas; López-Carril , Samuel (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Universities have a paramount goal of equipping students comprehensively for their impending professional journeys. A recognized method to achieve this objective is by nurturing students' professional competences. It is therefore valuable to ascertain whether this broad group of competences is being developed in students throughout the course of their studies. This article delves into the perceptions of students enrolled in Physical Activity and Sport Science university programs regarding the salient professional competences pivotal for their future careers, along with gauging the extent of development of each competence. Employing a cross-sectional quantitative design, this study engaged 166 participants from the University of Castilla-La Mancha (Spain) that completed an online questionnaire created ad hoc. Principal findings unveil that individuals with work experience discern social skills/interpersonal relations, teamwork, and oral and written communication as the most honed competences. Conversely, competences encompassing initiative and entrepreneurial spirit, working in an international context, and information management skills exhibit relatively lower development levels. Notably, noteworthy disparities surface between those with prior professional exposure and their inexperienced counterparts. Additionally, students in their third and fourth academic years perceive a more evolved skill set compared to their peers in the initial year of study.